Developing an Integrated Diversity Management Navigation System - binti Abdul Razak, Munira; bin Mohd Ramli, Najmuddin; Wei Xian, Kang; Suraya binti Wan Nik, Wan; binti Ali, Zuraina (International Journal of Engineering and Technology, 2018)
The initiatives of constructive alignment to overcome the TRIPLE CHALLENGES; to embed, engage and entice the technical and engineering students in University Malaysia Pahang (UMP) to learn the university core courses of Ethnic Relations have brought both technical and operational challenges. The innovative solution is applying i-E.R.A.T as a 3-in-1 diversity management approach. Despite enticing studentsâ€™ learning interest through the adaptation of Edmodo as one of the e-learning tools, it also supports the universityâ€™s educational outcomes on team working, leadership and problem solving; which reflect the National Education Policy on social cohesion. The methodology used to measure the effectiveness of i-E.R.A.T is by performing data analysis via mandatory on-line survey questionnaire called E-Pat that required studentsâ€™ opinion on the criterion that is related to e-learning. The focus group (FG) as respondents were collected from the four sections registered in the researcherâ€™s class of UHM 2022 Ethnic Relations course in Semester 1, session 2015/2016 from a population of approximately two thousand (N=2000) students from 30 sections. The results of the studies showed that majority of the students comprise of more than 90% satisfied (is that, strongly agree and agree) with the implementation of i-E.R.A.T in the teaching and learning processes.Â Â Â